DCO-OFDM channel sounding with a SiPM receiver - Matthews, W; He, C; Collins, S (IEEE, 2021)
Orthogonal Frequency-Division Multiplexing (OFDM) is a popular modulation scheme, which requires a linear channel. Unfortunately, the most sensitive receivers for visible light communications, silicon photomultipliers (SiPMs), have a non-linear response. Despite this incompatibility, results from an easily implemented method of combining OFDM and SiPMs are shown to successfully limit the bit error rate to below the limit required by forward error correction.